1996
DOI: 10.1016/0895-7061(96)00019-2
|View full text |Cite
|
Sign up to set email alerts
|

Neither physical exercise nor α1- and β-adrenergic blockade affect plasma endothelin concentrations

Abstract: Endothelins (ET) are recently discovered vasoconstrictor agents released from endothelial cells and have been the object of intense investigation by researchers. Many of the factors that seem to influence the release of ET are modified by prolonged exercise. The purpose of this study was to investigate the effect of physical exercise on ET plasma concentrations and the effect of alpha- and beta-blockade on ET concentrations at rest and during exercise. Fifteen young volunteers (age 20-35 years) performed an ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

1998
1998
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 25 publications
1
6
1
Order By: Relevance
“…The finding in the present study of decreased plasma ET-1 levels after cycling is in agreement with the data of Richter et al [9], whereas others reported no change [19][20][21][22] or even an increase in ET-1 plasma concentrations in young athletes performing 30 min of strenuous cycling [8]. These discrepancies may be due to the small numbers of subjects investigated [21] or to differences in the protocols used, e.g., intensity of exercise [8], time of blood sampling after performance [20], or assays used for ET measurements [20,21].…”
Section: Discussionsupporting
confidence: 95%
“…The finding in the present study of decreased plasma ET-1 levels after cycling is in agreement with the data of Richter et al [9], whereas others reported no change [19][20][21][22] or even an increase in ET-1 plasma concentrations in young athletes performing 30 min of strenuous cycling [8]. These discrepancies may be due to the small numbers of subjects investigated [21] or to differences in the protocols used, e.g., intensity of exercise [8], time of blood sampling after performance [20], or assays used for ET measurements [20,21].…”
Section: Discussionsupporting
confidence: 95%
“…The exercise-induced increases in plasma ET-1 obtained in our study confirm other reports [3,4] but are not in agreement with the results of Cosenzi et al [22] who showed unchanged ET-1 concentrations after dynamic exercise in normotensive subjects. These discrepant results may be due, at least in part, to the different stimulation induced by isometric and ergometric exercises, and to the assay methods used in the studies.…”
Section: Discussioncontrasting
confidence: 65%
“…Evidence for the ET-1 system as a potential regulator of exercising muscle blood flow has come largely from assays with evidence both for (29) and against (13,27) increased circulating ET-1 as a consequence of exercise. However, the preferential abluminal release of ET-1 and low endogenous concentration have led to the suggestion that systemic plasma ET-1 levels may not accurately reflect local ET-1 concentration (21,35).…”
Section: Discussionmentioning
confidence: 99%